2006
DOI: 10.1038/sj.ijo.0803365
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between body mass index and health-related quality of life: comparing the EQ-5D, EuroQol VAS and SF-6D

Abstract: Background: No other studies have compared the relationship between body mass index (BMI) and health-related quality of life (HRQL) on more than one utility measure. Estimating the HRQL effects of obesity on a (common) utility scale enables the relative cost-effectiveness of interventions designed to alleviate obesity to be estimated. Objective: To examine the relationship between BMI and HRQL according to the EQ-5D, EuroQol visual analogue scale (EQ-VAS) and SF-6D. Methods: Patients aged X45 years at one UK g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
162
6
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(204 citation statements)
references
References 42 publications
30
162
6
3
Order By: Relevance
“…Numerous cross-sectional studies have affirmed that compared to normal-weight individuals, obese individuals are more likely to have a poorer level of physical HRQoL [8][9][10][11][12][13][14][15][16][17]22,25,30,31,34,37]. Our study results confirmed that BMI is inversely associated with physical SF-12 summary score.…”
Section: Cross-sectional Association Between Bmi and Hrqolsupporting
confidence: 82%
See 2 more Smart Citations
“…Numerous cross-sectional studies have affirmed that compared to normal-weight individuals, obese individuals are more likely to have a poorer level of physical HRQoL [8][9][10][11][12][13][14][15][16][17]22,25,30,31,34,37]. Our study results confirmed that BMI is inversely associated with physical SF-12 summary score.…”
Section: Cross-sectional Association Between Bmi and Hrqolsupporting
confidence: 82%
“…In overweight and obese individuals, the physical SF-12 summary score decreased with increasing BMI whereas no such association was found in normalweight individuals. Several studies identified the highest levels of physical HRQoL among normal-weight adults [8][9][10][11]13,16,17,30,54]. However, other studies showed significantly poorer physical HRQoL only in obese but not in overweight individuals [14,15,31,37].…”
Section: Cross-sectional Association Between Bmi and Hrqolmentioning
confidence: 97%
See 1 more Smart Citation
“…Consequently, the CI of depth of obesity can also be interpreted as the distribution (according to income) of excess mortality that is associated with obesity. Results from several studies conducted in the United States (Jia and Lubetkin 2005; Sach et al 2007; Finkelstein et al 2010) indicate that health‐related quality of life decreases approximately quadratically with BMI above the obesity threshold. Thus, the CI of severity of obesity can also be thought of as approximately reflecting the distribution (according to income) of quality of life lost due to obesity.…”
Section: Methodsmentioning
confidence: 99%
“…reported that the higher the BMI, the worse the HRQL of individuals compared to those with normal BMI (30). Cameron and cols.…”
Section: Pain and Quality Of Life In Obese Patientsmentioning
confidence: 99%